Transillumination of palm for peripheral intravenous cannulation in an infant with difficult venous access - Shrestha, Gentle Sunder; Acharya, Binita; Tamang, Sushil (Journal of Society of Anesthesiologists of Nepal, 2015)
Establishing venous access can be technically difficult in paediatric patients. Alternatives to intravenous access like central venous cannulation or venous cutdown carry a higher risk of complications. We report a case of successful intravenous access in an infant with anticipated difficulty, by performing transillumination of palm using a torch light. Journal of Society of Anesthesiologists of Nepal 2015; 2(1): 31-33